Induced Pluripotent Stem Cell-Derived Parathyroid Organoids Resemble Parathyroid Morphology and Function - Senkal-Turhan, Selinay; Bulut-Okumus, Ezgi; Aydin, Muhterem; Turkmen, Nese Basak; Taslidere, Asli; Sahin, Fikrettin; Dogan, Aysegul (Wiley, 2024)
The primary role of the parathyroid glands is to maintain calcium homeostasis through the secretion of parathyroid hormone (PTH). The limited proliferative capacity and differentiation of parathyroid cells hinder the generation of cell therapy options. In this study, parathyroid organoids are successfully generated from human-induced pluripotent stem cells (hiPSCs). At the end of the 20 days of differentiation, the parathyroid organoids exhibited distinct parathyroid morphology. Stereomicroscope, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) analysis demonstrated the 3D arrangement of the cell layers in which intracellular structures of parathyroid cells resemble human parathyroid cellular morphology. Comprehensive molecular analyses, including RNA sequencing (RNA-Seq) and liquid chromatography/mass spectrometry (LC-MS/MS), confirmed the expression of key parathyroid-related markers. Protein expression of CasR, CxCr4, Gcm2, and PTH are observed in parathyroid organoids. Parathyroid organoids secrete PTH, demonstrate active intercellular calcium signaling, and induce osteogenic differentiation via their secretome. The tissue integration potential of parathyroid organoids is determined by transplantation into parathyroidectomized rats. The organoid transplanted animals showed significant elevations in PTH-related markers (CasR, CxCr4, Foxn1, Gcm2, and PTH). PTH secretion is detected in organoid-transplanted animals. The findings represent a significant advancement in parathyroid organoid culture and may offer a cellular therapy for treating PTH-related diseases, including hypoparathyroidism. iPSC-derived parathyroid organoids express PTH-related markers at the protein and gene levels. The transplantation of parathyroid organoids into parathyroidectomized rats shows their functional activity and tissue integration capability. iPSC-derived parathyroid organoids successfully release PTH both in vitro and in vivo. Parathyroid organoid technology may improve defective parathyroid function and related diseases. image
Keywords: 3D culture; hypoparathyroidism; organoid; parathyroid; parathyroid organoid; pluripotent stem cell